2010
DOI: 10.3149/jms.1803.249
|View full text |Cite
|
Sign up to set email alerts
|

Male Counseling Psychologists in Academia: An Exploratory Study of Their Experience in Navigating Career and Family Demands

Abstract: Male counseling psychology faculty (N = 83) were surveyed regarding their perceptions and experiences of an academic career and their efforts in navigating family and work roles. Results of this exploratory investigation showed that the majority (77%) of the participants had no regrets about their decision to pursue a career in academia, and 60% believed that they would give priority to family if a conflict between work and family commitment occurred. Participants noted several challenges of academia, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although there is less research, studies on academic fathers suggest that they too experience similar challenges when combining work and family life (Philipsen & Bostic, 2010;Marotte et al, 2011;Dillon, 2012) and that they face pressure when attempting to be both a successful academic and a good father (Duan et al 2010;Gould & Lovato, 2019;Reddick et al 2012;Sallee, 2012). However, the literature is clear that the challenges are greater for mothers, due to the physical demands of pregnancy and childbirth, gendered expectations of family obligations, and the ongoing inequality with which working women take on the 'second shift' (Hochschild, 1989) of home care and childcare (Misra et al 2012;O'Meara & Campbell, 2011;Thun, 2019;Wolf-Wendel & Ward, 2006), even within dual-career households (Erickson, 2005).…”
Section: What the Literature Tells Us About Academic Work And Parenthoodmentioning
confidence: 99%
“…Although there is less research, studies on academic fathers suggest that they too experience similar challenges when combining work and family life (Philipsen & Bostic, 2010;Marotte et al, 2011;Dillon, 2012) and that they face pressure when attempting to be both a successful academic and a good father (Duan et al 2010;Gould & Lovato, 2019;Reddick et al 2012;Sallee, 2012). However, the literature is clear that the challenges are greater for mothers, due to the physical demands of pregnancy and childbirth, gendered expectations of family obligations, and the ongoing inequality with which working women take on the 'second shift' (Hochschild, 1989) of home care and childcare (Misra et al 2012;O'Meara & Campbell, 2011;Thun, 2019;Wolf-Wendel & Ward, 2006), even within dual-career households (Erickson, 2005).…”
Section: What the Literature Tells Us About Academic Work And Parenthoodmentioning
confidence: 99%
“…Researchers have examined similar demographic, occupational, and family characteristics that influence the level of WFC experienced by mental health professionals (e.g., Duan, Brown, & Keller, ; Olarte, ). Kalliath, Hughes, and Newcombe () found that social workers experienced time‐, strain‐, and behavior‐based WIF and FIW in a sample of 439 social workers.…”
Section: Wfcmentioning
confidence: 99%
“…For workplace setting, women favored working in a private practice setting because of the work flexibility found within that environment, as well as the ability to match work schedules with their children's school schedules (Olarte, ). Family characteristics that influence female mental health professionals' experience of WFC include partner support, age of children, and time spent in family activities (Duan et al, ; Y. Lin, ; Olarte, ). Researchers found that spouse and partner support predicted WIF, and counseling professionals reported seeking social support as a means to cope with conflict between work and family roles (Brown & Duan, ; Duan et al, ; Hermann et al, ).…”
Section: Wfcmentioning
confidence: 99%
See 1 more Smart Citation